Conversion of asymptomatic infection to symptomatic visceral leishmaniasis: A study of possible immunological markers - Das, Vidya Nand Rabi; Bimal, Sanjiva; Siddiqui, Niyamat Ali; Kumar, Ashish; Pandey, Krishna; Sinha, Sanjay Kumar; Topno, Roshan Kamal; Mahentesh, Vijay; Singh, Ashish Kumar; Lal, Chandra Shekhar; Singh, Subhankar Kumar; Das, Pradeep (PLOS Neglected Tropical Diseases, 2020)
Author summary The most threatening form of leishmaniasis is human visceral leishmaniasis, which is caused by L. donovani in Indian subcontinent. The disease accounts for huge annual burden of infectious disease in India. Efforts towards disease elimination programme are far beyond satisfaction and there is need to re-strengthen health monitoring, surveillance programme in endemic areas. There is a greater need to identify asymptomatic individuals amongst endemic healthy control by active surveillance programme. Further, except a few, many asymptomatic subjects become sero-negative without developing VL due to strong inherent cellular immunity possessed by them. This study enumerates use of rK39, DAT and quantitative PCR(qPCR) in asymptomatic detection and then evaluate immunological biomarkers(Adenosine deaminase, IFN-γ, TNF-α and IL-10) which help in disease conversion to symptomatic VL, at 6 month follow- up. Follow–up analysis revealed that antibody testing with rK39 (3.24%), DAT (8.33%) had poor agreement with disease conversion. By qPCR, we could identify the level of parasitemia, and collectively with serology, the test detected 23.80% of asymptomatic cases converted into disease. The level of ADA and IL-10 remained consistently high during conversion. IFN-γ became high in asymptomatic infection but became low on conversion, whereas, no significant change in level of TNF-α was observed at both stages of disease. Thus by use of qPCR, concomitantly with DAT over rK39+ sorted endemic healthy control may be employed for early case detection. Adenosine is produced by ecto-nucleotide during L.donovaniinfection, has been previously reported and in parallel to this study we conclude that determination of adenosine deaminase level (ADA) might help identify early cases with more tendency to convert into disease. This will help to boost health monitoring programme to eradicate Kala-azar in Bihar, India.